Konflik Agraria di Pedesaan: (Studi Kasus Eksploitasi Minyak dan Gas Bumi oleh Exxon Mobil Cepu Limited Terhadap Tanah Kas Desa) - Miftakhur Rokhman Habibi; Achmad Safiudin; Jihan Rusdiana (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2020)
This article aims to find out what factors cause agrarian conflicts and how to know the efforts to resolve agrarian conflicts according to agrarian law No. 5 of 1960 and the laws and regulations relating to agrarian affairs. The results of the study concluded that: first, the existence of the support of the Village Government towards Exxon Mobil Cepu Limited, lacked support from the village community in the use of village treasury land and the lack of communication established between the EMCL, the Village Government and the Village Community. And Second, Law No. 5 of 1960 which imposed a resolution through a court process and outside the court could not resolve the conflict. The new conflict can be resolved by using Regional Regulation No. 23 of 2011 concerning the acceleration of the growth of exploration and exploitation and processing of oil and gas in Bojonegoro Regency, which regulates employment, land use and Corporate Social Responsibility (CSR) programs.